2022
DOI: 10.1021/acs.energyfuels.2c00084
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Liquid Nitrogen Fracturing for Unconventional Oil and Gas Development: A Review

Abstract: Liquid nitrogen (LN 2 ) fracturing is an anhydrous fracturing technology that enhances coal permeability and supports unconventional oil and gas exploitation. In this Review, we provide a systematic review of five aspects of LN 2 fracturing. They are the history of the technology's development, research topics, factors influencing fracturing efficiency, fracturing mechanism, and engineering processes and systems. Liquid nitrogen fracturing transforms coal and rock pore structure through mechanisms such as low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…The cement then solidifies in the annulus to form a protective film, which allows drilling to continue until it reaches the target layer horizontally. After the completion of the drilling operations, the on-site disassembly of the drilling rig is followed by the cleaning of the wellbore using a mixture of water and gel injected by a workover rig [113].…”
Section: Lnf Low-permeability Reservoir Modelmentioning
confidence: 99%
“…The cement then solidifies in the annulus to form a protective film, which allows drilling to continue until it reaches the target layer horizontally. After the completion of the drilling operations, the on-site disassembly of the drilling rig is followed by the cleaning of the wellbore using a mixture of water and gel injected by a workover rig [113].…”
Section: Lnf Low-permeability Reservoir Modelmentioning
confidence: 99%
“…Many scientific and engineering innovations, such as jet engines, drug delivery, fluidized bed reactors, aerobic granular sludge, and nuclear turbines, are premised on the understanding of fluid flow [1][2][3]. Flows in pipes and channels of various geometries are common in applications, and they are usually classified as Couette or Poiseuille flow.…”
Section: Introductionmentioning
confidence: 99%
“…Coal, a primary natural resource, still takes the lead in China’s energy structure at present. In order to ensure the efficient and steady development of society and economy, the total mining amount of coal resources has always remained at a high level. , However, with the long-term mining for many years, the shallow resource reserves are on the verge of exhaustion, thus ushering in the chapter of deep mining year by year . However, gas disasters are more serious at deeper coal seams. In response, pre-extraction of coal seam methane is the most effective engineering method to ensure safe and efficient mining, in which case the extracted methane can also be employed as clean energy . By comparing shallow coal seams with deep ones, it is found that the difference in stress is the biggest factor causing different disasters and extraction difficulties.…”
Section: Introductionmentioning
confidence: 99%